2020
DOI: 10.1111/jog.14408
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of laparotomy results in breast cancer patients with gynecological pathologies

Abstract: Aim: The aim of the study was to evaluate the results of the laparotomies due to gynecological pathologies in breast cancer patients and to assess the distribution of gynecological pathologies and the clinical and laboratory findings contributing to the diagnosis. Methods: This study was conducted between years 2002 and 2011 at Hacettepe University Hospital. We obtained information about 86 consecutive breast cancer patients, including age, time of diagnosis and pathology of breast cancer, hormone receptor sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Following this, cases featuring AUB were recorded in 28 instances (16.9%). In extant literature, AUB surfaces in approximately 50% of premenopausal cases and 25% of postmenopausal cases [10][11][12][13]. Notably, the preponderance of cases within our study was situated in the premenopausal period, and the routine gynecological surveillance of breast cancer patients is more frequent within our country due to medical practices.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Following this, cases featuring AUB were recorded in 28 instances (16.9%). In extant literature, AUB surfaces in approximately 50% of premenopausal cases and 25% of postmenopausal cases [10][11][12][13]. Notably, the preponderance of cases within our study was situated in the premenopausal period, and the routine gynecological surveillance of breast cancer patients is more frequent within our country due to medical practices.…”
Section: Discussionmentioning
confidence: 62%
“…While the prevalence of endometrial polyps within the general population fluctuates between 0-10%, patients undergoing tamoxifen treatment face an elevated risk, with incidence rates ranging from 6-42% [9][10][11][12]. Although endometrial polyps are benign, the likelihood of malignant transformation among endometrial polyps in the broader population is approximately 2% during the premenopausal phase and 5% during the postmenopausal phase.…”
Section: Discussionmentioning
confidence: 99%
“…Tamoxifen used in breast cancer patients with its low estrogenic effect on the uterine corpus, may cause epithelial and non-epithelial uterine corpus lesions such as polyps, hyperplasia, cancer, and uterine sarcoma (8,9). Mostly seen endometrial pathology in breast cancer patients using tamoxifen has been reported as endometrial polyp, this rate is approximately 8-44% in the previous studies (8,10).…”
Section: Discussionmentioning
confidence: 97%